Colombian death certificate data quality (Colombia Medica, 2018)
Objective: To evaluate overall quality of death certification and quality of cancer mortality certification in Colombia.Methods: Classic validity indexes were described through simple percentages for each department and five cities: Bogotá, Cali, Manizales, Pasto and Bucaramanga. A factorial analysis of principal components was performed in order to identify non-evident relationships.Results: 984,159 deaths were analyzed, 164,542 corresponding to cancer deaths. 93.7% of the overall mortality was properly certified. Most errors were due to signs, symptoms and ill-defined conditions. 92.8% of the cancer deaths were properly certified. Ill-defined cancers site certification prevailed as the most frequent cause of error.Conclusions: Colombia showed improvement in all indicators of quality certification. Given the high performance of quality indicators for overall death and cancer death certification, it is considered that mortality data can be used in the cancer incidence estimation process.